Strategies to overcome DC dysregulation in the tumor microenvironment - Mestrallet, Guillaume; Sone, Kazuki; Bhardwaj, Nina (Frontiers in Immunology, 2022)
Dendritic cells (DCs) play a key role to modulate anti-cancer immunity in the tumor microenvironment (TME). They link innate to adaptive immunity by processing and presenting tumor antigens to T cells thereby initiating an anti-tumor response. However, subsets of DCs also induce immune-tolerance, leading to tumor immune escape. In this regard, the TME plays a major role in adversely affecting DC function. Better understanding of DC impairment mechanisms in the TME will lead to more efficient DC-targeting immunotherapy. Here, we review the different subtypes and functions of DCs in the TME, including conventional DCs, plasmacytoid DC and the newly proposed subset, mregDC. We further focus on how cancer cells modulate DCs to escape from the host’s immune-surveillance. Immune checkpoint expression, small molecule mediators, metabolites, deprivation of pro-immunogenic and release of pro-tumorigenic cytokine secretion by tumors and tumor-attracted immuno-suppressive cells inhibit DC differentiation and function. Finally, we discuss the impact of established therapies on DCs, such as immune checkpoint blockade. Creative DC-targeted therapeutic strategies will be highlighted, including cancer vaccines and cell-based therapies.